Model Perhitungan Pendanaan Program Pensiun Manfaat Pasti Menggunakan Metode Projected Unit Credit - Jessica Delianti; Onoy Rohaeni (Jurnal Riset Matematika, 2022)
Abstract. The defined benefit pension program is a program organized by the Pension Fund. The calculation of defined benefit pension plan funds is carried out using the actuarial calculation method which calculates the cash value of pension benefits, normal contributions, and actuarial obligations. This study uses the projected unit credit method where the benefits are calculated according to the services provided up to the date of calculation. Based on the calculation results, the normal contribution for participants with the same basic salary and different years of service has a difference of while for participants with a basic salary and years of cooperation there is a difference of where participants with the longest working period and the largest basic salary will pay a larger contribution with smaller installments every year. The amount of the actuarial obligation will be equal to the value of the pension benefit to be received. Likewise, the value of pension benefits, for participants with the same basic salary and different years of service, there is a difference of, while for participants with different basic salaries and years of service there is a difference of . Thus, the basic salary affects the cash value of the pension benefit more than the length of service. Abstrak. Program pensiun manfaat pasti merupakan suatu program yang diselenggarakan oleh lembaga Dana Pensiun. Perhitungan pendanaan program pensiun manfaat pasti dilakukan menggunakan metode perhitungan aktuaria yang menghitung nilai tunai manfaat pensiun, iuran normal, dan kewajiban aktuaria. Penelitian ini menggunakan metode projected unit credit dimana besar manfaatnya dihitung sesuai dengan jasa yang telah diberikan sampai dengan tanggal perhitungan. Berdasarkan hasil perhitungan bahwa iuran normal untuk peserta dengan gaji pokok sama dan masa kerja berbeda memiliki selisih 5% sedangkan untuk peserta dengan gaji pokok berbeda dan masa kerja sama memiliki selisih 34% dimana peserta dengan masa kerja terlama dan gaji pokok terbesar akan membayar iuran lebih besar dengan cicilan lebih kecil tiap tahun. Besarnya kewajiban aktuaria akan sama besar dengan nilai manfaat pensiun yang akan diterima. Begitu juga dengan nilai manfaat pensiun, untuk peserta dengan gaji pokok sama dan masa kerja berbeda memiliki selisih sedangkan untuk peserta dengan gaji pokok berbeda dan masa kerja sama memiliki selisih . Dengan demikian besar gaji pokok lebih mempengaruhi nilai tunai manfaat pensiun dibandingkan dengan masa kerja.